Prospective observational study of carbon-ion radiotherapy for non-squamous cell carcinoma of the head and neck in Gunma University. Issue 3 (May 2022) - Musha, Atsushi; Kubo, Nobuteru; Okano, Naoko; Kaminuma, Takuya; Kawamura, Hidemasa; Sato, Hiro; Takayasu, Yukihiro; Shino, Masato; Nikkuni, Osamu; Ida, Shota; Shirai, Katsuyuki; Saitoh, Jun-ichi; et al.
Abstract: Objective: Data on the long-term outcomes of carbon-ion radiotherapy for non-squamous cell carcinomas are rare. Gunma University has been utilizing carbon-ion radiotherapy as a treatment for head and neck cancer since 2010. This study aimed to evaluate the long-term efficacy and safety of carbon-ion radiotherapy for the head and neck. Methods: We prospectively evaluated 35 patients with non-squamous cell carcinoma who underwent carbon-ion radiotherapy at Gunma University Heavy Ion Medical Center between 2010 and 2014. The 5-year local control, overall survival, and progression-free survival rates were evaluated. Results: The median age was 59 years (range, 31–77 years), and the median follow-up time was 65 months (range, 6.1–98.8 months). Overall, 32 and 3 patients received 64.0 Gy (relative biological effectiveness) and 57.6 Gy (relative biological effectiveness) in 16 fractions, respectively. Adenoid cystic carcinoma was the most dominant histopathological type (n = 21 patients, 60 %). The 5-year local control, progression-free survival, and overall survival rates were 74.5 %, 53.2 %, and 81.3 %, respectively. Nine patients had local recurrence, and six patients died. Adverse events included acute grade 3 radiation mucositis (Common Terminology Criteria for Adverse Events version 4.0) in 8 patients; this was improved immediately with conservative therapy. Late grade 4 adverse events were observed, including two cases of visual loss and one case of brain necrosis. No grade 5 adverse events were observed. Conclusion: Carbon-ion radiotherapy achieves excellent local control and overall survival rates in non-squamous cell carcinoma patients with expected adverse events.